1991
DOI: 10.1538/expanim1978.40.4_523
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Function of Food-restricted Germfree and Specific Pathogen-free Mice

Abstract: The effects of food restriction on immune function was investigated in germfree (GF) and specific pathogen-free (SPF) mice. They were maintained from five weeks of age under either full-fed or food-restricted conditions to 4.5 grams per day (equivalent to approximately 80% of full-fed intake) of a commercial diet. Longest survival rate was attained in food-restricted SPF mice followed by food-restricted GF, full-fed GF, and full-fed SPF animals. Food-restricted GF mice showed shorter survival rate than their S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Germ-free mice live longer, weigh less, and show decreased basal metabolic rate than mice with conventional microbiota [ 48 , 49 ]. In agreement with our findings of significant goblet cell loss, it has been reported that germ-free mice have fewer and smaller goblet cells in the cecum than conventional mice and that recolonization improves their number [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Germ-free mice live longer, weigh less, and show decreased basal metabolic rate than mice with conventional microbiota [ 48 , 49 ]. In agreement with our findings of significant goblet cell loss, it has been reported that germ-free mice have fewer and smaller goblet cells in the cecum than conventional mice and that recolonization improves their number [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…An overlap between life span, CR, and the microbiota in both rats and mice has been previously reported. Both CR and ablation of the microbiota increased the median life span of mice (138) and rats (134). However, the combination of CR and microbiome ablation did not have an additive effect on life span, suggesting an overlapping mechanism in the regulation of host longevity.…”
Section: The Microbiota and Host Metabolismmentioning
confidence: 92%